PREVALENCE OF SCHISTOSOMA HAEMATOBIUM INFECTION AMONG PRIMARY SCHOOL CHILDREN IN FASKARI AND FUNTUA LOCAL GOVERNMENT AREAS OF KATSINA STATE, NIGERIA - Bello, Sagir; Eberemu, E. C.; Orpin, J. B.; Ya’u, S. (FUDMA Journal of Sciences, 2024)
Schistosomiasis is a water-borne parasitic disease caused by Schistosoma; the digeic trematode found in the blood vessels of a man and livestock. This study was conducted to determine the prevalence of schistosoma haematobium infection among the Primary Schools pupils in Faskari and Funtua Local Government Areas of Katsina State. A total of 496 of urine samples were collected from children of 8 Primary Schools in the study areas; 4 from each local government. A questionnaire was used to collect socio-demographic and other exposure information to explore Schistosoma infection for urine, and urine sedimentation microscopic technique was used for sample analysis. Data were expressed in prevalence (%) and subjected to Chi-square analysis at p < 0.05. Out of the 496 children assessed, 160 (32.2%) were positive for urinary schistosomiasis. The prevalence is significantly (p
Keywords: Faskari; Funtua; Prevalence; Primary school pupils; Schistosoma haematobium; Urine sample